THE IMPACT OF DIGITALIZATION ON REDUCING CORRUPTION IN THE ECONOMY - Rakhmatjanov Lazizkhan Turabayevich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Modern society is facing one of the most serious social problems – the spread of corruption in all spheres of the economy. Moreover, this problem requires a comprehensive and systematic approach to overcome it, including the active participation of the state, organizations and citizens. The state’s anti-corruption policy is actively developing and increasingly intersects with the development of digital technologies. Publications devoted to the prevention of corruption usually focus on the analysis of a system of measures aimed at preventing, detecting and eliminating corruption. This study is devoted to the use of such a tool in the fight against corruption as digitalization. Digitalization in the activities of public authorities is a complex process that involves a number of problems that need to be resolved, some of which are discussed in this paper. The use of modern digital technologies and the practice of electronic public administration are one of the effective tools of anti-corruption policy in the digital space. Today, the development, adoption and implementation of modern legislative frameworks for the introduction and application of innovative digital anti- corruption technologies seem relevant.